Key features of illicit economies in African conflicts: Insights from the reports of UN Panels of Experts - Judith Vorrath; Laura Marcela Zu\~niga (Stiftung Wissenschaft und Politik (SWP), 2022)
There are currently a significant number of protracted armed conflicts worldwide. Illicit economies and their links to violent actors are frequently cited as reasons for their persistence. Drug cultivation, production, and trafficking in places as diverse as Afghanistan, Colombia, and Myanmar have been garnering attention recently since they can undermine peace processes and contribute toward rising levels of insecurity. Nevertheless, it is particularly difficult to grasp the situation in conflict zones and understand the networks of internal and external actors linked to illicit economies due to the limited information base. This also holds true for the violent conflicts in Mali, the Democratic Republic of Congo (DRC), and the Central African Republic (CAR) that have been going on for extended periods of time. However, since United Nations (UN) sanctions apply in all three contexts, there are extensive and regularly available sources of information provided by the reports of the UN Panels of Experts that monitor sanctions implementation. These investigative teams provide valuable insights into illicit economies in conflict zones and their links to peace and security. Looking at the reports for Mali, the DRC, and CAR from the last five years helps to identify some common patterns that defy simple solutions, but that can also show entry points for action.
Keywords: 320